Model Kemitraan Pemerintah dan Lembaga Keagamaan dalam Pendidikan Kerukunan: Studi Kasus Desa Karang Delanggu Klaten - Jaenuri; Ali Hamidi (IIQ An Nur Yogyakarta, 2026)
This study analyzes the model and effectiveness of strategic partnerships between religious institutions and the government in community education programs based on harmony values in Karang Village, Delanggu District, Klaten, as a response to the multicultural challenges of the Republic of Indonesia (NKRI) based on Pancasila and Quranic teachings regarding unity in diversity. Utilizing a qualitative method with a socio-anthropological approach involving in-depth interviews, participant observation, and documentation, the study finds that these partnerships are oriented toward the collective goal of creating a harmonious, prosperous, and spiritual community. Partnership solidarity is maintained through practical strategies such as regular consultations, fair task distribution, and the selection of neutral and comforting study themes and preachers, driven by a shared belief in the blessings of togetherness. The significant impact of this partnership includes increased social harmony, the practice of tolerance, and citizens' awareness in upholding the public good, proving that strategic synergy between the government and religious leaders is highly effective in advancing harmony-based community education.